1991
DOI: 10.1007/bf01741596
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin(hydrazone)-antibody conjugates require internalization and intracellular acid hydrolysis for antitumor activity

Abstract: Adriamycin hydrazone (ADM-Hzn) immunoconjugates have previously been shown to exhibit antibody-directed antitumor activity in vitro and in vivo. In this report, the biological and biochemical properties of the mAb and linker were investigated. Conjugates prepared with two antibodies 5E9 [anti-(transferrin receptor)] and G28.1 (anti-CD37), (which internalize from the surface of target cells following binding) were more cytotoxic in vitro and had greater antitumor activity against Daudi B lymphoma tumor xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…However, these improvements are not curative, and resistance or relapse after treatment remains significant in CD20-positive disease. Anti-CD20 mAbs linked to cytotoxics (21), plant toxins (23), or to immunoliposomes containing Dox (22) were ineffectual avenues for drug delivery to the cell interior. Surprisingly, anti-CD20 conjugated to the antimitotic MMAE has showed significant antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these improvements are not curative, and resistance or relapse after treatment remains significant in CD20-positive disease. Anti-CD20 mAbs linked to cytotoxics (21), plant toxins (23), or to immunoliposomes containing Dox (22) were ineffectual avenues for drug delivery to the cell interior. Surprisingly, anti-CD20 conjugated to the antimitotic MMAE has showed significant antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-drug conjugates of anti-CD20 have been evaluated and generally found to be ineffective. Anti-CD20 Dox conjugates (21), and more recently a rituximab-liposomal Dox (22) and anti-CD20-ricin A-chain conjugate, were not effective against CD20 positive cells (23). These results were partially attributed to differences in CD20 trafficking because other conjugates could induce modulation and internalization of mAb/antigen com-plexes, whereas a comparable effect was not observed with anti-CD20 (24).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a fragment was detected by mass spectrometry at m/z 581.2 (1+), which might be assigned to <EHWK-OH peptide, indicating the cleavage of the amide bond between the side chain of 4 Lys and the fatty acids [10,27]. However, the unambiguous identification of this fragment and of the free SCFA release requires further investigations.…”
Section: Enzymatic Stability/degradation Of Bioconjugatesmentioning
confidence: 99%
“…In the case of the reported bioconjugates, an oxime bond was formed between the C13 keto group of daunorubicin and the aminooxyacetyl group of the GnRH-III derivatives. The oxime bond is chemically stable between pH 3 and 8 [25], as well as under in vitro and in vivo biological experimental conditions [26]. Moreover, the daunorubicin-GnRH-III bioconjugates must possess increased stability in the presence of digestive enzymes present in stomach and intestine in order to be suitable for oral administration.…”
Section: Enzymatic Stability/degradation Of Bioconjugatesmentioning
confidence: 99%
“…In the same year Pastan and colleagues described the delivery of Pseudomonas exotoxin-antiTfR antibody conjugates into cellular endosomes [49]. Subsequent stu-dies have confirmed that the Tf delivery pathway is very flexible in accommodating transport of both small drugs [16][17][18][19][20][21][22][23][24][25][26], such as adriamycin, and structures [72][73][74][75][76] such as Tf-coated liposomes.…”
Section: Tf and Tfr Conjugates For Improved Uptake Into Cellsmentioning
confidence: 99%